Sum, sumu, sumon, and somon (Plural: sumd) are the lowest level of administrative division used in China, Mongolia, and Russia. The word sumu is a direct translation of a Manchu word niru, meaning ‘arrow’ Countries such as China and Mongolia, have employed the sumu administrative processes in order to fulfil their nations economic, social and political goals. This system was acted in the 1980s after the Chinese Communist Party gained power in conjunction with their growing internal and external problems. The decentralisation of government included restructuring of organisational methods, reduction of roles in rural government and creation of sumu’s.
Hello all,
I'm in the process of learning about 3 phase power and how to wire loads to a generator. I've searched high and low with as many sentence structures as I could think of in the google search bar and I can't seem to find the answers I'm looking for. I'm really hoping you guys can...
My interest is on the (highlighted part in yellow ) of finding the partial fractions- Phew took me time to figure out this out :cool:
My approach on the highlighted part;
i let
##(kr+1) =x ##
then, ##\dfrac{1}{(kr+1)(kr-k+1)} = \dfrac{1}{x(x-k)}##
then...
##(1+x)^n=1+C_1x+C_2x^2+C_3x^3...+C_nx^n##
Let ##x=1##, hence ##2^n=1+C_1+C_2+C_3...+C_n## which is equal to the sum of the coefficients.
I originally thought the sum of the coefficients would be ##2^n-1## since the very first term ##1## is just a number and has no variable. But apparently...
Hi! I am having trouble finalizing this problem.
The interval is given so we know that a = 1 and b = 2. From there you can figure out that ∆x = 1/n, xiR = 1 + i/n.
Using logarithmic properties, I rearranged the expression and wrote (1 + i/n)(1/n)ln[(n + i)/n].
I can guess that the function is...
Hi! I understand that this is an expanded Riemann sum but I'm having trouble determining its original form. I don't actually have any ideas as to how to find it, but I know that once I determine the original form of the Riemann sum, I will be able to figure out the values for a, b, and f.
If...
Problem Statement : The statement appeared on a website where a different problem was being solved. I got stuck at the (first) statement in the solution that I posted above 👆. Here I copy and paste that statement from the website, which I cannot show :
Attempt : To save time typing, I write...
Lemma
Let f be a bounded function on [a,b]. If P & Q are partitions of [a,b] and P ##\subseteq## Q , then
L(f,P) ##\leq## L(f,Q) ##\leq## U(f,Q) ##\leq## U(f,P) .
Question is "How can P have bigger upper darboux sum than Q while it is a subset of Q"
I want to know if there is any proper relation between the angles of a vector with the three dimensional coordinate axes,
if the angles are ,α , β and γ,
will the sum of α, β and γ be 180 degress
that is α + β + γ = 180°,m finding the same to be true in a 2 D case where α + β = 90° and γ =...
Hi, I'm struggling with understanding the idea of tensor product and direct sum beyond the very basics. I know that direct sum of 2 vectors basically stacks one on top of another - I don't understand more than this . For tensor product I know that for a product of 2 matrices A and B the tensor...
Attempt;
##\dfrac{1}{r(r+1)(r+2)} -\dfrac{1}{(r+1)(r+2)(r+3)}=\dfrac{(r+3)-1(r)}{r(r+1)(r+2)(r+3)}=\dfrac{3}{r(r+1)(r+2)(r+3)}##
Let ##f(r)=\dfrac{1}{r(r+1)(r+2)}##
##f(r+1)= \dfrac{1}{(r+1)(r+2)(r+3)}##
Therefore ##\dfrac{3}{r(r+1)(r+2)(r+3)}## is of the form ##f(r)-f(r+1)##
When...
My attempt;
##r^2+r-r^2+r=2r##
Let ##f(r)=(r-1)r## then it follows that ##f(r+1)=r(r+1)## so that ##2r## is of the form ##f(r+1)-f(r)##.
When
##r=1;## ##[2×1]=2-0##
##r=2;## ##[2×2]=6-2##
##r=3;## ##[2×3]=12-6##
##r=4;## ##[2×4]=20-12##
...
##r=n-1##, We shall have...
From my physical problem, I ended up having a sum that looks like the following.
S_N(\omega) = \sum_{q = 1}^{N-1} \left(1 - \frac{q}{N}\right) \exp{\left(-\frac{q^2\sigma^2}{2}\right)} \cos{\left(\left(\mu - \omega\right)q\right)}
I want to know what is the sum when N \to \infty. Here...
I've came across the two following theorems in my studies of Probability Generating Functions:
Theorem 1:
Suppose ##X_1, ... , X_n## are independent random variables, and let ##Y = X_1 + ... + X_n##. Then,
##G_Y(s) = \prod_{i=1}^n G_{X_i}(s)##
Theorem 2:
Let ##X_1, X_2, ...## be a sequence of...
Hi !
In a Feynman diagram, can we consider that the propagator specifying the transition amplitude of a particle (let's say, of a "real" electron, or of a "virtual" photon) between two points or two vertices, is in fact itself the sum of a multiplicity of probability amplitudes, each one...
Since we are adding numbers produced according to a fixed pattern, there must also be
a pattern (or formula) for finding the sum.
Hi, We use this method to find the ##S_n##. I don't understand how the sum will also be in a pattern. Can someone please explain this line in bold?
I am refreshing on this; of course i may need your insight where necessary...I intend to attempt the highlighted...this is a relatively new area to me...
For part (a),
We shall let ##f(x)=\dfrac{1}{x(2-x)}##, let ##g(x)## be the even function and ##h(x)## be the odd function. It follows...
im thinking i should just integrate (binominal distribution 1-2000 * prime probability function) and divide by integral of bin. distr. 1-2000.
note that I am looking for a novel proof, not just some brute force calculation.
(this isn't homework, I am just curious.)
Hello.
As is known, we can neglect high-order term in expression ##f(x+dx)-f(x)##. For ##y=x^2##: ##dy=2xdx+dx^2##, ##dy=2xdx##.
I read that infinitesimals have property: ##dx+dx^2=dx##
I tried to neglect high-order terms in integral sum (##dx^2## and ##4dx^2## and so on) and I obtained wrong...
Hello,
I would like to know, if there's a closed form solution to the following problem:
Given a sum of say, 3 sines, with the form y = sin(a.2.PI.t) + sin(b.2.PI.t) + sin(c.2.PI.t) where a,b,c are constants and PI = 3.141592654 and the periods in the expression are multiplication signs, what...
Dear Colleagues
I posted the same post in the group of Analysis. Perhaps it should have been posted here. It is a finite series for which I am seeking the sum. I tried using MATHEMATICA which did not work. Someone told me MAPLE will do it. So if one has it, I shall be thankful. All you have to...
How do I merge ##x^n + \displaystyle\sum^x_{k=1} \frac{d^k}{d^kx} \frac{x^ny^k}{k}##? I tried changing the denominator of the summand to ##k+1## and make ##k## go from zero, but I had to divide by zero when k equaled one.
I got something like this, but I'm not sure it is correct, because if it has the same order of convergence as trapezoidal rule which is 2, it should yield the same result as trapezoidal rule but mine doesn't (?).
For example sin(x) for [0,1], n with trapezoidal rule = 0.420735...
With my own...
Find question and solution here
Part (i) is clear to me as they made use of,
$$\sum_{r=n+1}^{2n} u_r=\sum_{r=1}^{2n} u_r-\sum_{r=1}^{n} u_r$$
to later give us the required working to solution...
...
##4n^2(4n+3)-n^2(2n+3)=16n^3+12n^2-2n^3-3n^2=14n^3+9n^2## as indicated.
My question is on...
I am refreshing on this...Have to read broadly...i will start with (b) then i may be interested in alternative approach or any correction that may arise from my working. Cheers.
Kindly note that i do not have the solutions to the following questions...
For (b), we know that,
say, if ##x=α##...
Let ## n ## be an integer.
Now we consider two cases.
Case #1: Suppose ## n ## is even.
Then ## n=2k ## for some ## k\in\mathbb{N} ##.
Thus ## n^{5}=(2k)^{5}=32k^{5}\equiv 0 \pmod 4 ##.
Case #2: Suppose ## n ## is odd.
Then ## n=4k+1 ## or ## n=4k+3 ## for some ## k\in\mathbb{N} ##.
Thus ##...
We have a matrix ##M = \ket{\psi^{\perp}}\bra{\psi^{\perp}} + \ket{\varphi^{\perp}}\bra{\varphi^{\perp}}##
The claim is that the eigenvalues of such a matrix are ##\lambda_{\pm}= 1\pm |\bra{\psi}\ket{\varphi}|##
Can someone proof this claim? I have been told it is self-evident but I've been...
Proof:
Let ## a>5 ## be an integer.
Now we consider two cases.
Case #1: Suppose ## a ## is even.
Then ## a=2n ## for ## n\geq 3 ##.
Note that ## a-2=2n-2=2(n-1) ##,
so ## a-2 ## is even.
Applying Goldbach's conjecture produces:
## 2n-2=p_{1}+p_{2} ## as a sum of two primes ## p_{1} ## and ##...
Proof:
Suppose ## p ## and ## p+2 ## are twin primes such that ## p>3 ##.
Let ## p=2k+1 ## for some ## k\in\mathbb{N} ##.
Then we have ## p+(p+2)=2k+1+(2k+1+2)=4k+4=4(k+1)=4m ##,
where ## m ## is an integer.
Thus, the sum of twin primes ## p ## and ## p+2 ## is divisible by ## 4 ##.
Since ##...
Hi there.
Let's say I have the following relationship:
x = a + b*z + c*y
z is distributed normally
y is distributed according to a different distribution, say exponential
Is there a way to figure out what is the distribution of x?
Thanks!
Summary:: summation of the components of a complex vector
Hi,
In my textbook I have
##\widetilde{\vec{E_t}} = (\widetilde{\vec{E_i}} \cdot \hat{e_p}) \hat{e_p}##
##\widetilde{\vec{E_t}} = \sum_j( (\widetilde{\vec{E_{ij}}} \cdot {e_{p_j}}*) \hat{e_p}##
For ##\hat{e_p} = \hat{x}##...
Proof:
Suppose n is an integer such that ## n>11 ##.
Then n is either even or odd.
Now we consider these two cases separately.
Case #1: Let n be an even integer.
Then we have ## n=2k ## for some ## k\in\mathbb{Z} ##.
Consider the integer ## n-6 ##.
Note...
I can't understand how this approximation works ##\sum_{k=0}^m\left(\frac{k}{m}\right)^n\approx\int_0^m\left(\frac{x}{m}\right)^ndx\tag{1}##Can you please help me
Hello, guys!
I have a question that need help!
A number with 17 digits is chosen and the order of its digits is inverted, forming a new number, These two numbers are then added up. Show that the sum contains at least one even number.
Hi,
I'm wondering if I have an expression for the scalar magnetic potential (V_in) and (V_out) inside and outside a magnetic cylinder and the potential is continue everywhere, which mean ##V^1 - V^2 = 0## at the boundary. Does it means that ##V^1 - V^2 = V_{in} - V_{out} = 0## ?
For part (i),
##(x-α)(x-β)=x^2-(α+β)x+αβ##
##α+β = p## and ##αβ=-c##
therefore,##α^3+β^3=(α+β)^3-3αβ(α+β)##
=##p^3+3cp##
=##p(p^2+3c)##
For part (ii),
We know that; ##tan^{-1} x+tan^{-1} y##=##tan^{-1}\left[\dfrac...
For part a,
We have ##α+β=b## and ##αβ =c##. It follows that,
##(α^2 + 1)(β^2+1)=α^2β^2+α^2+β^2+1)##
=##α^2β^2+(α+β)^2-2αβ +1##
=##c^2+b^2-2c+1##
=##c^2-2c+1+b^2##...
Given are non-negative integer variables ##x##, ##y## and ##z##. I am trying to deduce the absolute difference between a certain value of ##C=x^2+y^2+z^2## and the very next smallest increase in ##C## possible.
I'd like to do this so I can (dis)prove the following:
Whether small absolute...
Problem statement : I copy and paste the statement of the problem from the text.
(Given ##\boldsymbol{a+b+c=0}##)
Attempt : I am afraid I couldn't make any meaningful progress. With ##a = -(b+c)##, I substituted for ##a## in the whole of the L.H.S, both numerators and denominators. I multiplied...
Problem Statement : Let me copy and paste the problem as it appears in the text :
Attempt : I haven't been able to make any significant attempt at solving this problem, am afraid. I tried to reduce all the higher submultiple angles ##2\theta, 4\theta, 8\theta## into ##\theta##, but the...